Assistive technology for relieving communication lumber between hearing/speech impaired and hearing people - Akmeliawati, Rini; Bailey, Donald; Bilal, Sara Mohammed Osman Saleh; Demidenko, Serge; Gamage, Nuwan; Khan , Shujjat; Ye, Chow Kuang; Ooi, Melani; Gupta, Gourab Sen (The Institution of Engineering and Technology (IET), 2014)
This study proposes an automatic sign language translator, which is developed as assistive technology to help the hearing/speech impaired communities to communicate with the rest of the world. The system architecture, which includes feature extraction and recognition stages is described in detail. The signs are classified into two types: static and dynamic. Various types of sign features are presented and analysed. Recognition stage considers the hidden Markov model and segmentation signature. Real-time implementation of the system with the use of Windows7 and LINUX Fedora 16 operating systems with VMware workstation is presented in detail. The system has been successfully tested on Malaysian sign language.